Some Write to the Future : Essays on Contemporary Latin American Fiction - Dorfman, Ariel (Book collections on Project MUSE., 1991)
Formerly exiled Chilean author Ariel Dorfman, one of Latin America's greatest writers and a major literary figure of the twentieth century, is known for such critically acclaimed works as the novel Widows and the play Death and the Maiden. A master of various literary forms, this collection draws together Dorfman's critical essays on contemporary Latin American writing. Spanning more than twenty years and arranged in chronological order, each essay is devoted to a single author--Miguel Angel Asturias, Jorge Luis Borges, José Maria Arguedas, Alejo Carpentier, Gabrial Garcia Márquez, Roa Bastos--and one final essay looks at the "testimonial" or concentration camp literature from Chile.Praise for Ariel Dorfman"One of the most important voices coming out of Latin America."--Salman Rushdie"A remarkable writer . . . writing out of a very different cultural perspective from comfortable American readers."--Digby Diehl, Los Angeles Herald Examiner"One of the six greatest Latin American novelists."--Jacobo Timmerman, Newsweek.